2008
DOI: 10.1007/bf03055276
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of ostracod (Crustacea) biofacies on the continental shelf off south-east Trinidad, western central Atlantic Ocean, suggest the location of an offshore river-induced front within the Orinoco Plume

Abstract: Thirty two seafloor samples were taken over an area of 3600 km 2 off south-east Trinidad (water depths 38-102 m), north-east of the Orinoco Delta. A total of 7097 ostracod carapaces and valves from 37 species were picked from them. Total recovery was co-dominated by Bairdoppitata dorsoangutata and Brad#ya ex gr. dictyon, with lesser Radimella ovata, Loxoconcha sp. 2 s e n s u BREMAN, 1982 and Costa variabilicastata recticostata. Cluster analysis revealed four biofacies approximately perpendicular to the bathym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The complete disappearance of temperate species was placed at 15ºS, while the northern boundary of the Brazilian Province is still unclear due to lack of data from a large area which includes Guyana, Suriname and French Guyana, and the scarcity of data on marine ostracods off Venezuela and Colombia. However, Wilson (2007Wilson ( , 2008 observed that 12 out of the 37 shallow-water ostracod species registered in Trinidad and Tobago, also occur in the Brazilian Province, as follows: Bairdopillata dorsoangulata, Bythoceratina carmoi, Callistocythere fossulata, Caudites nipeensis, Costa variabilicostata recticostata, Cytherura sp. (= Cytherura duracina Coimbra, Carreño & Michelli, 1999), Gangamocytheridea dictyon, Kangarina ancyla, Paracytheridea tschoppi, Pellucistoma ex gr.…”
Section: Biogeographymentioning
confidence: 99%
“…The complete disappearance of temperate species was placed at 15ºS, while the northern boundary of the Brazilian Province is still unclear due to lack of data from a large area which includes Guyana, Suriname and French Guyana, and the scarcity of data on marine ostracods off Venezuela and Colombia. However, Wilson (2007Wilson ( , 2008 observed that 12 out of the 37 shallow-water ostracod species registered in Trinidad and Tobago, also occur in the Brazilian Province, as follows: Bairdopillata dorsoangulata, Bythoceratina carmoi, Callistocythere fossulata, Caudites nipeensis, Costa variabilicostata recticostata, Cytherura sp. (= Cytherura duracina Coimbra, Carreño & Michelli, 1999), Gangamocytheridea dictyon, Kangarina ancyla, Paracytheridea tschoppi, Pellucistoma ex gr.…”
Section: Biogeographymentioning
confidence: 99%
“…The Savonette area lies within their Zone VI, which they characterize as occupying a sandy zone little influenced by Orinoco outflow. Wilson (2007, 2008) found ostracod biofacies off SE Trinidad to be arrayed perpendicular to bathymetric contours and concluded that this reflects the interplay of Amazon- and Orinoco-derived water along an estuarine front within the Orinoco Plume. The Ibis and Savonette Fields lay on opposite sides of this front, the Savonette Field being beneath surface water derived from the River Amazon.…”
Section: Previous Workmentioning
confidence: 99%
“…Planktonic and calcareous benthonic foraminifera are abundant, however, on the modern continental shelf and slope SE of the island (Drooger & Kaasschieter, 1958; Pocknall et al . 2001; Wilson, 2006, 2010) despite this area lying within the hyperpycnal Orinoco low-salinity plume (Agard & Gobin, 2000; Wilson, 2007, 2008 a ), so water clarity seems an unlikely mechanism to explain the agglutinated Miocene assemblage. Jones (1998) thought the exclusion of calcareous matter might either be (a) penecontemporaneous and due to elimination from surface water of marine phytoplankton, which serve as food for at least some planktonic and deep-water benthonic calcareous foraminifera, or (b) diagenetic and due to salinity stratification, which would reduce circulation and oxygenation of bottom waters, allowing dissolution of calcite by acids released from decaying organic matter.…”
Section: Introductionmentioning
confidence: 99%